2012
DOI: 10.4103/0019-5049.96309
|View full text |Cite
|
Sign up to set email alerts
|

Intubating conditions following rapid sequence induction with three doses of succinylcholine

Abstract: Background:The aim of this prospective, randomized, double-blind study was to compare tracheal intubating conditions and the duration of apnoea following administration of 0.4, 0.6 and 1.0 mg/kg of succinylcholine during simulated rapid sequence induction of anaesthesia.Methods:Anaesthesia was induced with fentanyl 2 μg/kg and propofol 2 mg/kg followed by application of cricoid pressure. Patients were randomly allocated to three groups according to the dose of succinylcholine administered (0.4, 0.6 or 1.0 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…One trial was not blinded and therefore judged to be at high risk of bias ( Figure S1 and S2) [23]. Two trials reported sources of authors' funding and conflicts of interest [24,26].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…One trial was not blinded and therefore judged to be at high risk of bias ( Figure S1 and S2) [23]. Two trials reported sources of authors' funding and conflicts of interest [24,26].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In three studies, patients were premedicated (Table 1) [21,23,25]. Three studies used a true RSI [21,23,24], and two a modified RSI [22,25]. All five used intravenous propofol 2 mg kg − 1 with a concomitant intravenous opioid for induction.…”
Section: Induction Techniquesmentioning
confidence: 99%
See 3 more Smart Citations